Modell zur Evaluation der Nachhaltigkeit im Tourismus - Job, Hubert (ERDKUNDE, 1996)
Since the Rio Conference in 1992, the term 'sustainability' has become common parlance. Recognition of the limits of the global ecosystem appears to be spreading. As a result workers in a wide variety of disciplines have been searching for strategies of sustainable development which will give equal consideration to the ecological, economic and social aspects of the problem, and which could therefore offer future generations a choice in their exploitation of resources. A major problem of current economic activity is the disregard of negative external effects, in the areas of both production and transport. The latter is of the utmost importance in tourism, since the generation of the product is not restricted to one situation, but rather implies mobility. If the development of tourism proceeds uninterrupted, this mobility will in its turn imply consumption of raw materials and pollution from exhaust emissions, etc. The object of this article is the development of an analytical tool which can produce evidence about the sustainability of leisure and tourist traffic. Previous attempts to promote environmentally neutral and socially responsible leisure and travel policies have been exclusively concerned with the providers. In contrast to that approach, the theoretical model presented here operates in a network of demand orientated indicators, which focuses on the traveller him/ herself and in particular his/her behaviour in the environment. The sustainability balance-sheet is based on a number of six strong indicators, which can be calculated from accessible and reliable data. It compares individual journeys on the basis of their eligible parts - the route to the destination, journeys within the destination areas, the accomodation, and the purpose of the journey and attempts to reflect all three dimensions of sustainability. Different regional classifications of area-types, initially on a global scale, can be kept in view by the choice of different indicators and sub-indicators. To guarantee the easy comprehension by the travellers, this tool will be pointed out as a star-shaped travel chart.